Investigation of Chagas disease within the same family: case study - Takamiya, Nayore Tamie [UNESP] (2020)
Chagas disease (CD) is a neglected endemic disease. Its classic form of transmission occurs through hematophagous triatomine insects. Its classic form of transmission occurs through hematophagous triatomine insects. There are cases of the disease in non-endemic regions that occur through alternative transmissions, as this possibility also exists. The aim of this study was to report a case among members of a same family (born and resident in Taquarituba, São Paulo, Brazil) diagnosed with CD. The family matriarch lived in a mud house in the countryside and reported contact with the triatomine during childhood. Two grown-up children are also seroreactive; both reported not having contact with the insect as children. Medical record analyzes and new laboratory tests were performed. Clinical history and recent tests have confirmed positivity for CD in the matriarch and her grown-up children. Parasitological techniques have shown negative results, evidencing that they are in the chronic form of the disease. Congenital transmission may have occurred between them, as well as the possibility of vector transmission by secondary species cannot be ruled out, since the patients come from a municipality considered endemic for CD in the past.